2016
DOI: 10.1371/journal.pone.0150344
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Search for Host Association Factors during Ovine Progressive Pneumonia Virus Infection

Abstract: Ovine progressive pneumonia virus (OPPV) is an important virus that causes serious diseases in sheep and goats with a prevalence of 36% in the USA. Although OPPV was discovered more than half of a century ago, little is known about the infection and pathogenesis of this virus. In this report, we used RNA-seq technology to conduct a genome-wide probe for cellular factors that are associated with OPPV infection. A total of approximately 22,000 goat host genes were detected of which 657 were found to have been si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Uncharacterized IFITM sequences were named as “IFITM3-like” if their initiation codons aligned with known IFITM3 genes and “IFITM1-like” if their start codon aligned with other IFITM1 genes. Table S1 shows IR-IFITM genes with evidence for function (21, 39, 42, 46, 80) which were used to analyse selection pressures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncharacterized IFITM sequences were named as “IFITM3-like” if their initiation codons aligned with known IFITM3 genes and “IFITM1-like” if their start codon aligned with other IFITM1 genes. Table S1 shows IR-IFITM genes with evidence for function (21, 39, 42, 46, 80) which were used to analyse selection pressures.…”
Section: Methodsmentioning
confidence: 99%
“…Ifitm3 knockout mice show enhanced morbidity after infection with IAV, alphaviruses, and flaviviruses (33, 34, 35, 36), and in humans, single nucleotide polymorphisms in IFITM3 , which may act by altering IFITM3 expression or subcellular distribution, have been associated with an increase in morbidity in IAV and HIV-1 infections (recently reviewed by references 37 and 38). Antiviral function has also been reported for IFITMs from diverse mammalian and avian species (39, 40, 41, 42, 43, 44), although little is known about the role of IFITMs in antiviral defense in these species and in shaping host range. Phylogenetic studies have shown that the IFITM gene family is evolutionarily conserved and characterized by gene duplication, copy number variation, and the presence of pseudogenes (2, 45).…”
Section: Introductionmentioning
confidence: 99%
“…The response of the cells was reduced by 24 h and was stable until 48 h. This was probably because the immune response of the cells achieved a balance with the replication of the virus. Some of the most differentially expressed genes, e.g., CCL2, CCL5, CCL20, IL6, IL9, and IL16, belonged to the chemokine ligands or interleukins families [ 56 ].…”
Section: Impact Of Viral Infections On Expression Of Cytokine Genementioning
confidence: 99%
“…Recently, genome-wide association studies (GWAS) determined an antiviral role of the host cellular restriction factor known as interferon-induced transmembrane protein 3 (IFITM3), highlighting the importance of the innate response in the fight against SRLV [ 59 ].…”
Section: Innate Immunitymentioning
confidence: 99%